2015
DOI: 10.1186/s12885-015-1320-z
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based cognitive behavioral therapy for sexual dysfunctions in women treated for breast cancer: design of a multicenter, randomized controlled trial

Abstract: BackgroundSexual dysfunction is a prevalent, long-term complication of breast cancer and its treatment and can be treated effectively with face-to-face sexual counselling. However, relatively few women actually opt for face-to-face sex therapy, with many women indicating that it is too confronting. Internet-based interventions might be a less threatening and more acceptable approach, because of the convenience, accessibility and privacy it provides. Recent studies have demonstrated the efficacy of internet-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 96 publications
1
37
0
1
Order By: Relevance
“…Although additional randomised controlled trials (RCTs) are needed to delineate the specific elements of psychosocial and mind-body interventions that promote particular aspects of sexual function, empirical evidence of their effectiveness continues to accumulate(Brotto, Mehak, & Kit, 2009;Brotto et al, 2010Brotto et al, , 2012Derzko, Elliott, & Lam, 2007;DuHamel et al, 2016;Dyer et al, 2016;Huffman et al, 2016;Hummel et al, 2015). Improvements in parameters of sexual function and QoL have been demonstrated with psychoeducation(Advani, Brewster, Baum, & Schover, 2017;Bober, Recklitis, Bakan, Garber, & Patenaude, 2015;Brotto et al, 2008;DuHamel et al, 2016;Schover et al, 2013), cognitive behavioural therapy (CBT;Brotto et al, 2010Brotto et al, , 2012Duijts et al, 2012;Hummel et al, 2015Hummel et al, , 2017, couples-based interventions, couples counselling(Brotto et al, 2010), targeted psychosexual therapy(Brotto et al, 2010;DuHamel et al, 2016), yoga-based interventions(Brotto et al, 2009) and mindfulness-based interventions(Brotto et al, 2012). Recently, interventions for post-cancer sexual dysfunction have been implemented using online formats, with demonstrated effects on sexual and relational functioning(Classen et al, 2013;Hummel et al, 2015Hummel et al, , 2017Van Lankveld, 2016;Schover et al, 2013).…”
mentioning
confidence: 99%
“…Although additional randomised controlled trials (RCTs) are needed to delineate the specific elements of psychosocial and mind-body interventions that promote particular aspects of sexual function, empirical evidence of their effectiveness continues to accumulate(Brotto, Mehak, & Kit, 2009;Brotto et al, 2010Brotto et al, , 2012Derzko, Elliott, & Lam, 2007;DuHamel et al, 2016;Dyer et al, 2016;Huffman et al, 2016;Hummel et al, 2015). Improvements in parameters of sexual function and QoL have been demonstrated with psychoeducation(Advani, Brewster, Baum, & Schover, 2017;Bober, Recklitis, Bakan, Garber, & Patenaude, 2015;Brotto et al, 2008;DuHamel et al, 2016;Schover et al, 2013), cognitive behavioural therapy (CBT;Brotto et al, 2010Brotto et al, , 2012Duijts et al, 2012;Hummel et al, 2015Hummel et al, , 2017, couples-based interventions, couples counselling(Brotto et al, 2010), targeted psychosexual therapy(Brotto et al, 2010;DuHamel et al, 2016), yoga-based interventions(Brotto et al, 2009) and mindfulness-based interventions(Brotto et al, 2012). Recently, interventions for post-cancer sexual dysfunction have been implemented using online formats, with demonstrated effects on sexual and relational functioning(Classen et al, 2013;Hummel et al, 2015Hummel et al, , 2017Van Lankveld, 2016;Schover et al, 2013).…”
mentioning
confidence: 99%
“…63 In a more recently published trial, Hummel found that intensive internet-based cognitive behavioral therapy was effective at improving sexual function and related outcomes in 169 breast cancer survivors meeting criteria for sexual dysfunction 56 according to the Diagnostic and Statistical Manual of Disorders-IV (DSM-IV). 64 Findings of these trials suggest that recent web-based counseling interventions are highly effective in breast cancer or breast and gynecologic cancer samples 63,65 although they need to be tested in populations of women with cancer-related sexual problems outside of breast and gynecologic cancer. Telephone-based behavioral interventions could be helpful for reaching patients across a range of ages and levels of internet use and have gained some preliminary evidence in colorectal and breast cancer samples, 66,67 although larger trials of such interventions are needed.…”
mentioning
confidence: 99%
“…Prior to the diagnosis and treatment of breast cancer, sexual dysfunction was not reported in 91.5% of pa-tients (6). The prevalence of sexual complications was estimated at 30% -100% using previous treatments and included decreased libido, sexual arousal, and vaginal lubrication, followed by dyspareunia and vaginal dryness (6,(13)(14)(15).…”
Section: Contextmentioning
confidence: 99%